THE ROLE OF INNOVATIVE TECHNOLOGIES IN THE PROCESS OF IMPROVING STUDENTS’ PROFESSIONAL-METHODICAL COMPETENCE - Matonat Pardayeva (International Scientific and Current Research Conferences, 2024)
The professional level and qualification of personnel working in the educational system of our republic, and continuous improvement of professional pedagogical competencies in accordance with the requirements of the time is considered one of the urgent issues of today. Article 46 of the newly revised Law of the Republic of Uzbekistan "On Education" describes the obligations of pedagogues: quality organization of educational activities; use of information and communication technologies, advanced and innovative forms and methods of teaching and upbringing; it is emphasized that they should regularly improve their qualifications and undergo periodic certification in terms of their suitability for the position they hold.